2017
DOI: 10.3168/jds.2016-11935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incomplete milking on milk production rate and composition with 2 daily milkings

Abstract: The primary aim of this study was to assess the effects of incomplete milking on milk secretion and milk composition at the quarter level. Twelve cows were enrolled beginning at 5 d in milk and remained on study through 47 d in milk. Half of each contralateral udder was incompletely milked (treatment), detaching the teat cup early to leave approximately 30% of the total milk yield behind. This target milk remaining in the gland was based on weekly calibration milking measurements of quarter total milk yield. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 20 publications
4
29
1
Order By: Relevance
“…Our study suggests that the SM Q for these treatments would have been on the order of 0.1 kg, 0.3 kg, and 0.6 kg, respectively. Penry et al (2017) and Kuehnl et al (2019) reported significantly lower milk production rates when early-lactation cows were severely undermilked, leaving about 1.4 kg of SM in a quarter. Our study suggests that MFR1.0 Q would produce a similar SM Q .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our study suggests that the SM Q for these treatments would have been on the order of 0.1 kg, 0.3 kg, and 0.6 kg, respectively. Penry et al (2017) and Kuehnl et al (2019) reported significantly lower milk production rates when early-lactation cows were severely undermilked, leaving about 1.4 kg of SM in a quarter. Our study suggests that MFR1.0 Q would produce a similar SM Q .…”
Section: Discussionmentioning
confidence: 96%
“…In an AMS, Krawczel et al (2017) saw no effect on SCC or milk yield when teat cup milk flow rate switch-point was increased from 0.06 kg/min to 0.48 kg/min at the quarter level. The study by Penry et al (2017) measured the milk left in the quarter, and thus it is not comparable with a specific milk flow rate switch-point used in other studies. As a reference, the studies by Edwards et al (2013) and Clarke et al (2008) reported increases in strip milk of approximately 0.3 L at the udder level when increasing the milk flow rate switch-point up to 0.8 kg/min.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In that study, however, the treatment was applied for a longer period (from 5 to 47 DIM) compared with our study (1-5 DIM). Moreover, due to the half-udder design used by Penry et al (2017), we could hypothesize the levels of galactopoietic hormones to be the same for both treated and control quarters; thus, the response observed in treated quarters in their study was possibly solely due to local quarter-level response (rather than local and central changes). In our study, the treatment could have induced both local and central responses, but minimal differences in milk yield were observed between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although ran in a different species and with a different study design, the results observed by Wilde et al (1989) also support the findings of the current study, where a relatively short period of incomplete milking was used. A more recent study from Penry et al (2017), conducted in dairy cows, showed that an incompletely milked half-udder (defined as approximately 30% of total milk yield left behind at the end of milking) had lower milk production rate (0.73 kg/h) than a completely milked half-udder (0.97 kg/h), without an effect on milk composition. In that study, however, the treatment was applied for a longer period (from 5 to 47 DIM) compared with our study (1-5 DIM).…”
Section: Discussionmentioning
confidence: 99%